Wording Matters: Support for Women’s Reproductive Policies in the US - Hansen, Michael A. (Cambridge University Press (CUP), 2025)
The Supreme Court of the United States’ (SCOTUS) decision in Dobbs v. Jackson Women’s Health Organization removed the federal right to an abortion, thereby entrusting the states to decide the fate of women’s reproductive health care policies. The outcome activated pro-choice and pro-life groups in efforts to secure favorable policies in states. One tool that groups have utilized to gain support for their position involves selective framing of women’s reproductive policies, including careful selection of wording employed in popular referenda. Using a survey experiment, this study investigates how word/phrase choice influences support for women’s reproductive policies. Two general findings stand out. First, word/phrase choices significantly impact aggregate levels of support for policies. Second, predictor variables exhibit non-static relationships with support across statements. For example, some gender gaps were evident in support for general statements and pro-choice-leaning statements but absent for specific statements and pro-life-framed statements. These findings hold implications for elections on reproductive health policies.